Jednostki samorządu terytorialnego – podmioty wewnętrzne czy zewnętrzne polityk publicznych? - Jęczarek, Mateusz (Polityka i Społeczeństwo, 2020)
This article presents, on the basis of the classification of actors of public policy presented by Suwaj and Wenclik, local government entities involved in the implementation of public policies. Through examples of the functioning in practice, the image of the participants in local government is shown as “those that directly affect the shape of the (national) public policy, are directly involved in its creation”, a fact which results from belonging to the category of public administration. In turn, the remainder of the image is presented as local government entities “who are not directly involved in making decisions about the shape of public policy, although their opinions may be important in its shaping”. Such a view leads to the perception of municipalities, counties and provinces as entities “suspended” between the central authorities and the specific interests determined by local communities and the broadly understood local government sector.